KEMAMPUAN TRANSLASI DAN TRANSFORMASI REPRESENTASI MATEMATIS SISWA DALAM MENYELESAIKAN SOAL CERITA KONTEKSTUAL MATERI HIMPUNAN - Arifin, Muhammad Nur; Sugiatno, Sugiatno; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research aims to describe students’ translation and transformation ability on mathematical representation in solving contextual word problems of sets in class VIII SMP Negeri 18 Pontianak. The method that was use in this research is descriptive method with case study form. The subject of this research are 35 students. The data collection instrument that used is written test in essay and interview as the follow-up activity. The result of data analysis showed that the students’ translation ability on mathematical representation from the verbal representation to the symbol representation (sets symbol) is classified as very low with percentage 100%; students’ translation ability on mathematical representation from the symbol representation (sets symbol) to the visual representation (Venn diagram) is classified as very low with percentage 60%; students’ translation ability on mathematical representation from the verbal representation to the symbolic representation is classified as very low with percentage 100%; students’ transformation ability on mathematical representation in symbolic representation is classified as very low with percentage 51.43%; and students’ transformation ability on mathematical representation in verbal only a small part with percentage 40% which reached very high. Kata kunci : kemampuan translasi, kemampuan transformasi, soal cerita kontekstual, himpunan